Using selenomethionyl derivatives to assign sequence in low‐resolution structures of the AP2 clathrin adaptor. Issue 3 (1st March 2016) - Kelly, Bernard T.; Graham, Stephen C.; Owen, David J.
Abstract : A selenomethionine marker strategy allowed the identification of a region of disconnected electron density at low resolution and despite poor selenomethionine incorporation, thereby building a structural framework for understanding how the clathrin adaptor AP2 regulates clathrin binding in mammalian cells. Abstract : Selenomethionine incorporation is a powerful technique for assigning sequence to regions of electron density at low resolution. Genetic introduction of methionine point mutations and the subsequent preparation and crystallization of selenomethionyl derivatives permits unambiguous sequence assignment by enabling the placement of the anomalous scatterers (Se atoms) thus introduced. Here, the use of this approach in the assignment of sequence in a part of the AP2 clathrin adaptor complex that is responsible for clathrin binding is described. AP2 plays a pivotal role in clathrin‐mediated endocytosis, a tightly regulated process in which cell‐surface transmembrane proteins are internalized from the plasma membrane by incorporation into lipid‐enclosed transport vesicles. AP2 binds cargo destined for internalization and recruits clathrin, a large trimeric protein that helps to deform the membrane to produce the transport vesicle. By selenomethionine labelling of point mutants, it was shown that the clathrin‐binding site is buried within a deep cleft of the AP2 complex. A membrane‐stimulated conformational change in AP2 releases the clathrin‐binding site from autoinhibition, thereby linking clathrin recruitment to membrane localization.